Manganese Schiff Base Complexes, Crystallographic Studies, Anticancer Activities, and Molecular Docking - Ayodele Temidayo Odularu (Journal of Chemistry)
Choice of ligands is significant to successful synthesis of metal complexes (coordination compounds). This study reports the use of Schiff base as the right ligand to control the poor bioavailability and neurodegenerative toxicity challenges of manganese ion. In line with this study, document analysis was used as the methodological approach to evaluate the significance of Schiff base ligands in easing these manganese’s challenges and aligning the resultant coordination compounds (manganese Schiff base complexes) as therapeutic agents in anticancer studies. Report also involves crystallographic studies where single crystal X-ray crystallography was used as a chemical characterization technique. In addition, molecular docking studies, MOE2008, and AutoDock software were used to reveal the mode of interaction between the Schiff base and the manganese(II) and (III) ions, as well as scrutinizing the biological efficacy of the manganese(II) and manganese(III) Schiff bases coordination compounds as anticancer agents against some anticancer cell lines. Conclusion drawn was that manganese(II) and manganese(III) Schiff bases coordination compounds gave more active and potent activities than the corresponding Schiff bases. As a result, challenges of neurodegenerative toxicity and poor bioavailability of manganese ion were overcome, and the chelation therapy was fulfilled. Results from single crystal X-ray crystallography confirmed the successful synthesis of manganese(II) and manganese(III) Schiff bases coordination compounds and revealed the mechanism of reaction, while the molecular docking buttressed the biological activities of the Schiff base ligand and manganese Schiff base coordination compounds by portraying the structure activity relationship (SAR) between either Schiff base or the manganese Schiff base coordination compounds and the virtual cancer cell line (receptor protein), where hits were obtained for lead optimizations.